(untitled) (Revista Inclusiones, 2020)
Eradication of corruption as a phenomenon is possible only by means of cardinal rearrangement of the principles of the government control system operation where officials will not have a possibility to take advantage of their office and place citizens in conditions when they have to pay an official a bribe in favor of their interests. It was hard to fulfill for a long time but the appearance of Internet and egovernments made it possible in many countries throughout the world including Azerbaijan. The objective of this paper consists in revealing peculiarities of using the possibilities of digital economy in Azerbaijan to fight against corruption having deep socio-economic roots.